2019
DOI: 10.3390/en12102025
|View full text |Cite
|
Sign up to set email alerts
|

City-Level Features of Energy Footprints and Carbon Dioxide Emissions in Sichuan Province of China

Abstract: The sustainable development of the western region of China has always been essential to the national development strategy. The Western region has undertaken an industrial transfer from the Eastern and Central regions. Therefore, the CO2 emission intensity in the western region is higher than those of the Eastern and Central regions of China, and consequently its low-carbon development pathway has an important impact for China as a whole. Sichuan Province is not only the province with the highest CO2 emissions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Similar case was reported that carbon emissions of forest ecological products showed a fluctuating upward trend in Zhejiang Province [ 94 ] and Xinjiang Province [ 95 ], whereas it was regarded that urgent measures should be taken to significantly reduce greenhouse gas emissions in Shandong Province, a typical province of energy consumption [ 19 ]. However, there are also some cases that reported the characteristics and dynamics of carbon emissions and carbon sinks with emission reduction potential insights in economically developing areas of China [ 40 , 75 , 77 ]. These reports found that there was much reduction potential of carbon emissions with the carbon sink as well as carbon emissions per capita and carbon intensity in Chinese economically undeveloped and developing areas [ 40 , 75 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar case was reported that carbon emissions of forest ecological products showed a fluctuating upward trend in Zhejiang Province [ 94 ] and Xinjiang Province [ 95 ], whereas it was regarded that urgent measures should be taken to significantly reduce greenhouse gas emissions in Shandong Province, a typical province of energy consumption [ 19 ]. However, there are also some cases that reported the characteristics and dynamics of carbon emissions and carbon sinks with emission reduction potential insights in economically developing areas of China [ 40 , 75 , 77 ]. These reports found that there was much reduction potential of carbon emissions with the carbon sink as well as carbon emissions per capita and carbon intensity in Chinese economically undeveloped and developing areas [ 40 , 75 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also some cases that reported the characteristics and dynamics of carbon emissions and carbon sinks with emission reduction potential insights in economically developing areas of China [ 40 , 75 , 77 ]. These reports found that there was much reduction potential of carbon emissions with the carbon sink as well as carbon emissions per capita and carbon intensity in Chinese economically undeveloped and developing areas [ 40 , 75 , 77 ]. They also proposed that the government should provide a suitable economic growth and development range for the average gross domestic product growth rate, the proportions of primary industry and secondary industry, energy consumption intensity of secondary industry, and the urbanization [ 40 , 75 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations